PENGARUH KOMBINASI AROMATERAPI NEROLI DAN RELAKSASI NAPAS DALAM TERHADAP NYERI PERSALINAN KALA I DI PUSKESMAS GEYER I - Astuti , Lestari Puji; Ariana, Dhina Novi; Boediarsih, Boediarsih (Jurnal Kebidanan, 2024)
Labor’s pain is a physiology process, but overcoming labor’s pain can cause fatigue, extending the delivery, increase distress maternal, and increase the risk of post partum bleeding that cause the numbers of Maternal Mortality Rate. At the same time, labor’s pain can caused increasing the risk of severe asphyxia, cerebral injury, and infection of medical action. To minimized that risks, clients can accepted non pharmacological method such as the combination of aromatherapy and deep breath relaxation. Nerolli aromatherapy is a therapeutic action using flower of orange essential oil that have advantage as antispasmodic and mild sedative to relaxing the body. The aim of this research is to know about the effect of combination of nerolli aromatherapy and deep breath relaxation to labor’s pain in first stage of delivery in Puskesmas Geyer 1. This quantitative research used one group pre test post test design. The population are all of Mom’s that delivered her baby in Puskesmas Geyer 1 during January until February 2022. The sample of research are 17 respondents that used purposive sampling methods. Bivariat analysis are Wilcoxon exercise. The result of this research are labor’s pain in first stage had the median was 9 and deviation standard is 0,772. While labor’s pain after giving intervention had the median 3, and deviation standard 1,448. From statistical test result, we have p value about 0,000 so its mean there be a significant effect about giving combination of nerolli aromatherapy and deep breath relaxation to labor’s pain on first stage of delivery. Keywords: Aromatheraphy, Deep Breath Relaxation, Labor’s Pain